Analisis strategi bertahan wisata kuliner dan budaya lokal sebagai daya tarik wisata di Pasar Wit-witan Desa Alasmalang Kecamatan Singojuruh Banyuwangi - Lifa Ningrum, Nadiya; Yosi Mulyana Pratiwi; Nina Ruly Istiari (Innovative: Journal Of Social Science Research, 2024)
Culinary tourism is present as a support for tourism activities in an area. The existence of culinary tourism and local culture is a driver of tourism to promote and become a tourist attraction for tourists. In addition, culinary tourism and local culture can increase the economic wheels of the community around tourism. But in fact, only a few culinary and local cultural tourism can last for a long time, one of which is the date market located in Alasmalang Village, Singojuruh District, Banyuwangi. This date market is a local culinary market that prioritizes the authenticity of local culture so as to create its uniqueness compared to other culinary tours. This study focuses on the discussion of the analysis of the survival strategy of local culinary and cultural tourism as a tourist attraction in the Wit-witan Market, Singojuruh District, Banyuwangi, and has the aim of identifying the types and potentials of local culinary and cultural tourism in the Banyuwangi Wit-witan Market and the survival strategy of local culinary and cultural tourism owned by the Wit-witan Market as a tourist attraction. This research is a qualitative research with the object of research on culinary business actors and the culture of the date market in Banyuwangi. The research sampling technique uses purposive sampling. Data collection uses observation, interview, and documentation methods. Data analysis is carried out by means of data reduction, data presentation and conclusions. Furthermore, a data feasibility test is carried out and conclusions are drawn from the analysis and recommendations are provided in accordance with the reality in the field. In the end, this study resulted in an in-depth discussion related to the survival strategy owned by the date market in Singojuruh District, Banyuwangi which can also be a branding of Banyuwangi tourism and the output targeted in this study is publish in articles in accredited journals.